Narrative Focus in 300: Testimoniality and Violence in Central America - Bonilla Navarro, José Francisco (2023)
The novel 300, by Rafael Cuevas Molina, is analyzed here. Considering testimoniality as a discursive modality in Central American literature, we describe its relationship with the discursive framework of narrative texts that establish the relations between the traumatic processes of guerrilla and insurgency with the forms of construction of memories and disenchantments, including the problems of conceptualization, writing and narrative focalization as resources of textual semiosis. The latter is a strategy that presents a typology of polyphonic voices to elucidate the representation of violence in this novel, as one of the aesthetic-discursive specificities of the text.